Private rites eaudiobook A novel. - Armfield, Julia (Macmillan Audio, 2024)
"One of my favorite novels of the past few years." —Jeff VanderMeer, New York Times bestselling author of Annihilation From the award-winning author of Our Wives Under the Sea , a speculative reimagining of King Lear , centering three sisters navigating queer love and loss in a drowning world It's been raining for a long time now, so long that the land has reshaped itself and old rituals and religions are creeping back into practice. Sisters Isla, Irene, and Agnes have not spoken in some time when their father, an architect as cruel as he was revered, dies. His death offers an opportunity for the sisters to come together in a new way. In the grand glass house they grew up in, their father's most famous creation, the sisters sort through the secrets and memories he left behind, until their fragile bond is shattered by a revelation in his will. The sisters are more estranged than ever, and their lives spin out of control: Irene's relationship is straining at the seams, Isla's ex-wife keeps calling, and cynical Agnes is falling in love for the first time. But something even more sinister might be unfolding, something related to their mother's long-ago disappearance and the strangers who have always seemed unusually interested in the sisters' lives. Soon, it becomes clear that the sisters have been chosen for a very particular purpose, one with shattering implications for their family and their imperiled world. A Macmillan Audio production from Flatiron Books.